Minat belajar siswa pada tugas-tugas sekolah : Bagaimana peran Intensitas bermain gadget? - Salsabilla Adin Ardita; Tatik Meiyuntariningsih; Hetti Sari Ramadhani (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to prove that there is a negative correlation between the variable intensity of playing gadgets with students’ learning interest in school assignments. The participants in this study were 75 students from SDN Sukorejo grades V and VI. The sampling technique in this study used a purposive sampling technique. Data analysis technique uses Spearman’s Rho correlation. The results showed a correlation of -0.077 with a significance of 0.0512 (p>0.05). This means that the intensity of playing gadgets is not proven to be related to students’ learning interest in school assignments, so the hypothesis proposed in this study is rejected Keywords: intensity, gadgets, interest in learning, school assignments Abstrak Penelitian ini bertujuan membuktikan adanya korelasi negatif antara variabel intensitas bermain gadget dengan minat belajar siswa pada tugas-tugas sekolah. Partisipan dalam penelitan ini berjumlah 75 siswa dan siswi dari SDN Sukorejo kelas V dan VI. Teknik sampling dalam penelitian ini menggunakan teknik purposive sampling. Teknik analisis data menggunakan korelasi Spearman’s Rho. Hasil penelitian menunjukkan korelasi sebesar -0,077 dengan signifikansi 0,0512 (p>0,05). Artinya intensitas bermain gadget tidak terbukti berhubungan dengan minat belajar siswa pada tugas-tugas sekolah sehingga hipotesis yang diajukan dalam penelitian ini ditolak. Kata kunci : Intensitas, gadget, Minat Belajar, Tugas Sekolah